Thrombosis in the Uremic Milieu—Emerging Role of "Thrombolome". Issue 2 (24th June 2014) - Shashar, Moshe; Francis, Jean; Chitalia, Vipul
Abstract Chronic kidney disease (CKD) is characterized by retention of a number of toxins, which unleash cellular damage. CKD environment with these toxins and a host of metabolic abnormalities (collectively termed as uremic milieu) is highly thrombogenic. CKD represents a strong and independent risk factor for both spontaneous venous and arterial (postvascular injury) thrombosis. Emerging evidence points to a previously unrecognized role of some of the prothrombotic uremic toxins. Here, we provide an overview of thrombosis in CKD and an update on indolic uremic toxins, which robustly increase tissue factor, a potent procoagulant, in several vascular cell types enhancing thrombosis. This panel of uremic toxins, which we term "thrombolome" (thrombosis and metabolome), represents a novel risk factor for thrombosis and can be further explored as biomarker for postvascular interventional thrombosis in patients with CKD.